Foreign Portfolio Investment and Price Discovery of Indian Equity Stocks - De, Suddhasanta; Chakraborty, Tanupa (Indian Journal of Research in Capital Markets, 2018)
Speed of price correction is an indicator of market efficiency. In this paper, we tried to find whether the speed of price adjustment of Indian equity stocks, measured by Damodaran’s price adjustment coefficient (PAC), was indeed enhanced by foreign portfolio holdings. Applying the VAR Granger causality test, we found absence of any influence of FPI holdings in the speed of price corrections in Indian stocks and vice versa. We also observed that the speed of incorporation of stock level information was substantially lower than that of index level information, implying the existence of significant information asymmetry among different groups of investors and slow dissemination of firm specific information.